2022
DOI: 10.31764/jmm.v6i4.9547
|View full text |Cite
|
Sign up to set email alerts
|

Optimalisasi Learning Management System Di Pusat Kegiatan Belajar Masyarakat

Abstract: Abstrak: Kegiatan pengabdian ini dilatarbelakangi oleh proses pembelajaran yang kurang maksimal di saat pandemi atau proses pembelajaran yang dilakukan secara daring. Proses pembelajaran di Pusat Kegiatan Belajar Masyarakat (PBKM) Bhakti Luhur pada saat pandemi mengandalkan media sosial seperti whatsapp hasilnya kurang maksimal, sehingga capaian pembelajaran menurun. Berdasarkan temuan masalah ini tim pengabdi mengadakan pelatihan dan pendampingan dalam pemanfaatan Learning Management System (LMS) pada kegiata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Teachers also find it helpful to see 1056 Development of Learning Management System Model and … International Journal of Instruction, October 2023 • Vol.16, No.4 the progress of student learning because it has a ranking list. Students also claim to be enthusiastic about this ranking list because they can see and compare the learning progresses between themselves and their friends so that they can be more motivated to study harder (Kadafi et al, 2022). The effectiveness of using literacy-based thematic digital pedagogy models was also seen when students who took a quiz of 10 questions in 15 minutes.…”
Section: Effectiveness Of Learning Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers also find it helpful to see 1056 Development of Learning Management System Model and … International Journal of Instruction, October 2023 • Vol.16, No.4 the progress of student learning because it has a ranking list. Students also claim to be enthusiastic about this ranking list because they can see and compare the learning progresses between themselves and their friends so that they can be more motivated to study harder (Kadafi et al, 2022). The effectiveness of using literacy-based thematic digital pedagogy models was also seen when students who took a quiz of 10 questions in 15 minutes.…”
Section: Effectiveness Of Learning Toolsmentioning
confidence: 99%
“…Teachers also revealed that they had to try to make students understand first in accessing the LMS link at the beginning of learning. According to Kadafi et al, (2022) an assessment of the success of this program can be seen from: 1) The existence of learning administration is carried out online, 2) The existence of learning administration is carried out with the LMS, 3) Monitoring the presence of participants learning online, 4) Tracking the presence of participants learning is carried out with LMS, 5) Improving the quality of learning, 6) Learning is carried out online, 7) Utilization of Moodle-based LMS for synchronous and asynchronous learning, 8) Available guidebooks for using Moodlebased LMS, 9) Teachers are able to operate LMS for learning activities, and 10) Learning participants are able to use LMS for learning activities.…”
Section: Effectiveness Of Learning Toolsmentioning
confidence: 99%